2022
DOI: 10.3389/fmars.2021.737671
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Integration: The Needs and Challenges of Effective Coordination Within the Ocean Observing System

Abstract: Understanding and sustainably managing complex environments such as marine ecosystems benefits from an integrated approach to ensure that information about all relevant components and their interactions at multiple and nested spatiotemporal scales are considered. This information is based on a wide range of ocean observations using different systems and approaches. An integrated approach thus requires effective collaboration between areas of expertise in order to improve coordination at each step of the ocean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Through four-layer sub-functions, the information network level aims to establish a sensor network for the underlying sensors while setting up reasonable network communication protocols and scheduling control [12] . The aim is to ensure the effective transmission of massive data during real-time monitoring and improve end-to-end delay performance and energy efficiency to a certain extent.…”
Section: Information Network Levelmentioning
confidence: 99%
“…Through four-layer sub-functions, the information network level aims to establish a sensor network for the underlying sensors while setting up reasonable network communication protocols and scheduling control [12] . The aim is to ensure the effective transmission of massive data during real-time monitoring and improve end-to-end delay performance and energy efficiency to a certain extent.…”
Section: Information Network Levelmentioning
confidence: 99%
“…Furthermore, European seagrass is considered a key Biological Quality Element (BQE) for coastal and transitional waters under the European Union Water Framework Directive (WFD) (Foden & Brazier, 2007) and is part of several environmental descriptors under the Marine Strategy Framework Directive (MSFD). Monitoring of seagrass across the globe as well as in Europe is not sufficiently coordinated nor interoperable, which results in inadequate delivery of critical information and limits science‐based decision‐making (Moersberger et al, 2022; Révelard et al, 2022). However, seagrass is becoming more often included in management and conservation, and several management actions such as improvement of water quality, reduction of industrial sewage, and anchoring and trawling regulations have been shown to support seagrass recovery (de los Santos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The eGOOS is an evolving (and growing) system of complementary observing networks coordinated through the Observation Coordination Group (OCG) of the Intergovernmental Oceanographic Commission (IOC) of the United Nations Educational, Scientific and Cultural Organization (UNESCO), with monitoring support from joint World Meteorological Organization (WMO) -IOC OceanOPS center (Revelard et al 2021). Shipboard measurements allow versatile sampling and high-quality measurements, but come at higher cost and with more human and environmental limitations.…”
Section: Introductionmentioning
confidence: 99%